Design Arduino-Based Complete Sensor Trainer as A Learning Medium - Purnamawati Purnamawati; Muhammad Akil; Nuridayanti Nuridayanti (Universitas Negeri Makassar, 2022)
Abstract. The use of learning devices in public lectures is an absolute requirement to provide convenience and smooth learning in the teaching process. The purpose of this research is to create a complete sensor trainer based on Arduino. The sensor grouping used in this trainer consists of light sensors, temperature sensors, tilt sensors, colour sensors, sound sensors, GSM & GPS, and Accelerometers. The overall research procedure is to start from the manufacture of box trainer design, PCB layout design, box trainer creation, PCB layout creation, module trials, repair, and module installation. Based on the research procedure, the creation of this trainer consists of two parts namely hardware and software. Trainer trials are conducted by examining the voltage source on the power supply and connecting it to each sensor module according to the required amount of voltage. The sensor module is in good condition and works when the indicator light on the module is lighted. Next, create a basic Arduino IDE-based sensor value reading program to ensure that the sensor module can function as in its usability. The development of this trainer can be done by connecting sensor and controller devices with the internet so that the monitoring and controlling process can be done based on IoT